Surface Analysis of Fermented Wheat and Rice Starch Used for Coating Traditional Korean Textiles - Yu, Hye Hyun; Lee, Youngseo; Nam, Yun-Sik; Kim, Man-Ho; Lee, Kang-Bong; Lee, Yeonhee (MDPI Open Access Publishing, 2022)
Wheat and rice starches, traditionally used to stiffen fabric, become less contaminated and more antiseptic after fermentation for several years, thus enhancing their functional activity. In the present study, analytical techniques using particle size analysis, a gloss meter and a colorimeter were used to measure the physical properties of wheat and rice starches that had been fermented for 5 and 7 years, respectively. Their chemical contents and composition were determined by nutrient measurements and time-of-flight secondary ion mass spectrometry (ToF-SIMS). The ToF-SIMS spectra and ion images showed that fermented starch contained more carbohydrate and less lipid than fresh starch. The surface morphologies of the fermented starch granules and starch-coated textiles were examined by scanning electron microscopy and compared with the surface morphologies of fresh starch granules. The fermented wheat and rice starch granules were smaller and more rounded with a lower level of N-containing compounds (proteins) and exhibited more antiseptic properties than fresh starch granules. The results showed that physical measurements and chemical analysis were simple and complementary techniques for investigating traditional Korean starch materials and textiles.